Generation Z in the Kazakhstan Labor Market: Expectations, Motivation, and Management Approaches - Sydykova, Aidana; Boranbayeva , Ainur; Muratbekkyzy, Aliya; Bimendieva, Leyla (BUKETOV BUSINESS REVIEW, 2025)
This study aims to examine the work values and motivational drivers of Generation Z in Kazakhstan as they transition into the labour market. Using a structured survey administered to 104 university students and analysed with SPSS Statistics 29, the study explores how intrinsic, extrinsic, and social work values influence employment expectations and preferences. The findings show that while financial stability, job security, and career advancement are dominant extrinsic motivators, Gen Z respondents also prioritise supportive social environments, meaningful tasks, and personal development opportunities. Statistically significant differences were found between respondents with different geographic job preferences, indicating that aspirations for international employment correlate with stronger preferences for innovation, interdepartmental experience, and creative work settings. This study addresses a critical gap in the literature by offering empirical evidence from Kazakhstan, a context underrepresented in global discussions on youth employment. The findings offer practical insights for employers, HR professionals, and policymakers to design strategies that align with the expectations of a new workforce generation. Recommendations are made to support inclusive, flexible, and innovation-driven management practices suitable for Kazakhstan’s evolving labour landscape.